Task Complete: A gamified solution to exercise positive habits in players with Intellectual Disabilities - Michalichem, Pedro Afonso F.; Pereira, Leonardo Tórtoro; Rodrigues, Kamila Rios da Hora (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2024: Anais do XXIII Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2024.241189, 2024)
This paper describes creating and evaluating a gamified solution called Task Complete, which aims to support productivity and encourage positive habits in its players, especially people with Intellectual Disabilities. The solution transforms everyday tasks into motivational elements, engaging users through virtual rewards. It was designed following principles of User Centered Design, as well as developed and evaluated considering accessibility and usability requirements. The PENS model and Web Content Accessibility Guidelines (WCAG)1 were considered in the project, seeking to make the solution inclusive for various user profiles.